(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to study the relationship between investment spending on basic infrastructure sectors and the change in the number of workers in the Syrian economy during the period from 2000 to 2020, by following the error correction model (ECM). The model estimation results indicated that there is a long-term relationship between investment spending on infrastructure (as an independent variable) and employees (as a dependent variable) in Syria during the period under study. In addition, the results of the estimation of the simple linear regression model showed that the relationship is positive between the two studied variables and this is consistent with the economic theory. The results also proved that there was no short-term relationship between the two variables studied, that is, the spending that was directed to the infrastructure sectors in that period did not lead to job creation during the short-term period. Because of the destruction of the infrastructure and the exit of many factories and facilities from work, as a result of the results of the war that impeded the progress of the process of economic and sustainable growth and development.